Pengaruh Penggunaan Media Kartu Bergambar Terhadap Hasil Belajar Ilmu Pengetahuan Sosial Siswa Sekolah Dasar - Rahman, Syarifah Aeni (Pusat Pengembangan Pendidikan dan Bakat Indonesia, 2022)
The main problem in this research is whether the use of picture cards media affects the learning outcomes of social science in fifth-grade students at SD Inpres Sambung Jawa 1 in Makassar City. This study aims to determine the effect of using picture cards media on the learning outcomes of social science in fifth-grade students at SDN Sambung Jawa in Makassar City. The type of research is an experimental study with a Pre-Test Post-Test Design, which is an experiment that involves only one class as an experimental class without a control class, aimed at determining the effect of using picture cards media on the learning outcomes of social science in fifth-grade students at SD Inpres Sambung Jawa 1 in Makassar City for the academic year 2022/2023. The experimental unit in this study is 31 fifth-grade students. The results of this study indicate that a teacher who uses learning media with picture cards can improve students' learning outcomes positively. The use of picture cards media showed better learning outcomes than before the implementation of picture cards media on social science learning outcomes in fifth-grade students at SDN Sambung Jawa in Makassar City.